(3HjGf YdI bjGe GdCQV hSW GdeGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO aEf GdTjN GeQfi Cf CTQM dg GdePgH GdMb ai YdI bjGe GdGQV ai MjRg GdPi gh ajg HeG jbQH ef JUhQg hjRhd GdTHgI s
(3BNQgG (B:s
(3Ke COjQJ HbhI bGe GdTQGH hGdMLQ ai GdhSW hbGd HYVge Gf CLRGA GdGQV EfeG Edi GdGQV YTbkG HcdjJgG agPG eG MVQfG ai gPg GdSGYI ai GQGA GdbOeGA ai GdGQV hdfNJe GdQSGdI hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs